Análise econômica da “produção invisível” nos estabelecimentos agrícolas familiares no Projeto de Assentamento Agroextrativista Praialta e Piranheira, Município de Nova Ipixuna, Pará - MENEZES, Antonio José Elias Amorim de (2002)
This work discusses the importance of invisible production in the composition of total income of small farmers at the agricultural frontier in the Amazon, marked strongly by agrarian conflicts, as is the case of southeast Pará State. The data used in this study were obtained from field research undertaken with 78 small farmers of the Praialta and Piranheira Agroextractivist Settlement Project, Nova Ipixuna municipality, Pará, in 2001. The general objective of this work was to know in what form the invisible production contributes to composition of family income and to the reproduction strategy of small farm agriculture in the southeast of Pará State. The choice of farmers interviewed was intentional, so that it enabled the identification of agricultural income, as well as in the characterization of the production systems developed by these small farmers. This procedure allowed the elaboration of a typology of the production systems starting from some social, economic and agronomic indicators. The results of this research proved a strong participation of invisible production in the group of the activities of the family agriculture. Products with defined markets, have a part of the production retained for family consumption, non-markets products are directed exclusively to own consumption and, an important component, refers to the sale of family labour, essential in their survival strategy. An immediate conclusion is that the agricultural and extractive production is very superior to that being estimated or unknown in the official statistics. Knowledge of the participation of invisible production becomes important for the policymakers, first due to the under estimation of official statistical data, as much for the amount as for the non-inclusion of various products, produced or collected, in family agriculture, on or off the property. This way, it can be verified that the small farmers of the Praialta and Piranheira Agroextractivist Settlement Project possess an equivalent total income to 1,48 minimum wage/ month. It is interesting to highlight that the contribution of invisible production to family income reaches 0,28 minimum wage/month that represents 18,77%, of the total estimated income. The drainage of the autonomous non-agricultural income, from government welfare pensions, represents 10,55% of the farmers' monetary income, constituting an important factor of the local communities' sustainability. It is expected that these results are important to define public policies to increase the sustainability of frontier family agriculture estimated as more than 600 thousand family units in the Amazon, responsible for the largest portion of the chronic deforestation and burning.